Oblicz wartość liczbową wyrażenia :


a). 4x - (x + 6) + 4 dla x = jedna - trzecia
b). (x <do potęgi drugiej > +1) - ( x <do potęgi drugiej> - 2) + 10 dla x = 2 ,2
.C = ( a + 4b) - (5 + 2a) - (3b - 5) A = - 0,1 B = 0,2
D = ( -a do potęgi drugiej + 2ab - 1) + (a do potęgi drugiej - 4ab + 5) A = 1/4 B = 2

2

Odpowiedzi

2010-02-19T20:27:28+01:00
1.4x-x-6+4=3x-2
3x-2=1-2=-1
2.x²+1-(x²-2)+10=x²+1-x²+2+10=13
3.a+4b-5-2a-3b+5=-a+b=0,1+0,2=0,3
4.-1/16+1-1+1/16-2+5=3
1 4 1
  • Użytkownik Zadane
2010-02-19T20:28:32+01:00
A). 4x - (x + 6) + 4=4x-x-6=3x-6+4=3*⅓-6=1-6+4=-1

b). (x² +1) - ( x² - 2) + 10=x²+1-x²+2+10=13

.C = ( a + 4b) - (5 + 2a) - (3b - 5) =a+4b-5-2a-3b+5=-a+b=0,1+0,2=0,3

D = ( -a²+ 2ab - 1) + (a² - 4ab + 5)=-a²+2ab-1+a²-4ab+5= -2ab+4=-2*¼*2+4=-1+4=3
1 5 1